Improvisation Effectiveness in the Performance of the Actor in the Theatrical Show: مصطفى عباس خلف (Al-Academy, 2019)
Improvisation is that spontaneous automatic achievement which is formed by a new cognition that is not based on something prior to it or a previous cognition. It is instantaneous. Whereas in art, improvisation also inters in all types of applied and performance arts as a foundation for launching and initiating it in music, painting, cinema, television and theater. In order to study the improvisation of the actor, the researcher put forward a theoretical study that included two sections. The first section is (the improvisation concept) and the second section is (improvisation in the show). The researcher, in the research procedures, took an intentional sample that was represented by the theatrical show (Rehearsal in Hell Play) and after the analysis, he came out with a set of results the most important of which was that: The improvisation had an effect in creating astonishment in performance and breaking the boredom and this what characterized many scenes of the show that they diverged out of the traditional artificial performance.